PENGARUH PENGGUNAAN MODAL TERHADAP TINGKAT EFISIENSI YANG DI CAPAI OLEH BANK YANG GO PUBLIK DI BURSA EFEK JAKARTA - Yanti, . (Jurnal Ekonomi Pembangunan, 2009)
Purpose of this research is to know development of legal capital and level of efficiency which in reached by Bank which Go Public at Bursa Effect Jakarta and know legal capital influence to level of efficiency pads Bank which Go Public at Bursa Effect Jakarta. From result of panel data analysis shows CAR and LDR to have influence which are positive with level of efficiency. Test Result F indicates that dependent variables tied is good in simulation influential significant to level of efficiency and tee test result indicates that usage variable of legal capital which in the form of LDR partially had an effect on significant to level of efficiency